Profile of the Teachers of the Faculty of Sciences of the Information of the Universidad Autónoma de San Luis Potosí - Martínez Rider, Rosa María (2018)
The results of the characteristics of the teaching profile of the librarian at the Facultad de Ciencias de la Información of the Universidad Autónoma de San Luis Potosí are presented as part of an Ibero-American research project of the Library Education Seminar, coordinated by Phd. Lina Escalona Ríos at the Instituto de de Investigaciones Bibliotecológicas y de Información of the UNAM.The objective was to analyze the congruence between the teacher profile and the educational model that permeates the Information Management curriculum of the Facultad de Ciencias de la Información (FCI) of the Universidad Autónoma de San Luis Potosí (UASLP), México.